ANALISIS PENERAPAN SHARIA COMPLIANCE DALAM PRODUK PEMBIAYAAN AKAD MURABAHAH - Octasari, Astrie; Julia, J; Abubakar, Kirana (AL HUKMU: Journal of Islamic Law and Economics, 2023)
This study aims to describe the role of the Sharia Supervisory Board (DPS) towards sharia compliance and to analyze the application of sharia compliance in murabaha contract financing products. The research method used is normative legal research with a qualitative approach. In this study, researchers examined concrete legal regulations and substantial regulations accompanied by supporting literature in the form of literary sources that were relevant to the research object being discussed. The results of the study show that the existence of the Sharia Supervisory Board (DPS) is to guarantee and supervise Islamic banks so that they remain in the corridors of Islamic law. The role of the Sharia Supervisory Board (DPS) is very crucial in the implementation of sharia compliance in Islamic banks in Indonesia. The role of the Sharia Supervisory Board (DPS) at the technical level of banking operations is very important considering the duties, responsibilities and authorities they have. The Sharia Supervisory Board (DPS) in carrying out their duties can be active or responsive. The Sharia Supervisory Board (DPS) must actively supervise, collect data, analyze and correct various findings of sharia non-compliance in an Islamic bank. Financing with a murabaha contract that has been practiced by Islamic banking has deviated from several provisions in the DSN MUI Fatwa and there is a conflict with the legal terms of a sale and purchase agreement with a murabaha contract, namely the bank fully represents the customer to buy and receive goods from suppliers and gives the right to carry out deed of sale and purchase for and on behalf of the customer himself directly with the supplier. Islamic banks should first buy the object before the object is sold to the customer and also in this practice only one sale and purchase transaction, namely between the supplier and the customer. Based on DSN MUI Fatwa No. 04/DSN-MUI/IV/2000 concerning Murabahah, murabahah financing must occur in two sale and purchase agreements.